Financial accounting : IFRS - Weygandt, Jerry J.; Kieso, Donald E.; Kimmel, Paul D. (Hoboken, New Jersey : John Wiley & Sons, 2011)
* Explains the business reason for making accounting decisions * Introduces challenging accounting concepts with examples that are familiar * US public companies will have to follow International Financial Reporting Standards as of January 1, 2011, Weygandt's Financial Accounting: IFRS introduces these
1. Accounting in action -- 2. The recording process -- 3. Adjusting in accounts -- 4. Completing the account cycle -- 5. Accounting for merchandising operations -- 6. Inventories -- 7. Fraud, internal control and cash -- 8. Accounting for receivables -- 9. Plant assets, natural recourses and intangible assets -- 10. Liabilities -- 11. Corporations: organization, share transactions, dividends and retained earnings -- 12. Investments -- 13. Statements of cash flows -- 14. Financial statement analysis
Includes index
Keywords: Accounting -- Standards; International business enterprises -- Accounting